Innovative developments in design and manufacturing : advanced research in virtual and rapid prototyping : proceedings of the 4th International Conference on Advanced Research and Rapid Prototyping, Leiria, Portugal, 6-10 October 2009 - International Conference on Advanced Research and Rapid Prototyping (4th : 2009 : Leiria, Portugal); Bartolo, Paulo (Leiden, The Netherlands : CRC/Balkema, 2010)
Includes bibliographical references and index